Thermal comfort in air‐conditioned buildings in hot and humid climates – why are we not getting it right?. (27th January 2015) - Sekhar, S. C.
Abstract: While there are plenty of anecdotal experiences of overcooled buildings in summer, evidence from field studies suggests that there is indeed an issue of overcooling in tropical buildings. The findings suggest that overcooled buildings are not a consequence of occupant preference but more like an outcome of the HVAC system design and operation. Occupants' adaptation in overcooled indoor environments through additional clothing cannot be regarded as an effective mitigating strategy for cold thermal discomfort. In the last two decades or so, several field studies and field environmental chamber studies in the tropics provided evidence for occupants' preference for a warmer temperature with adaptation methods such as elevated air speeds. It is important to bear in mind that indoor humidity levels are not compromised as they could have an impact on the inhaled air condition that could eventually affect perceived air quality. This review article has attempted to track significant developments in our understanding of the thermal comfort issues in air‐conditioned office and educational buildings in hot and humid climates in the last 25 years, primarily on occupant preference for thermal comfort in such climates. The issue of overcooled buildings, by design intent or otherwise, is discussed in some detail. Finally, the article has explored some viable adaptive thermal comfort options that show considerable promise for not only improving thermal comfort in tropical buildings but are also energy efficient and could be seen as sustainable solutions.